Modul Persiapan Peran Menjadi Ibu terhadap Pengetahuan dan Keterampilan Volunteer Sayang Ibu - Maya Latifatul Masrurroh; Krisdiana Wijayanti; Lanny Sunarjo; Sri Sumarni; Yessy Arisman (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the effectiveness of the motherhood preparation module. This research method uses Research and Development (R&D) and Quasy Experimental Pretest and Posttest Design. The results showed that the level of knowledge of "volunteer loves mother" in the category of good knowledge was 53.8% in the pretest and 100% in the posttest. "Volunteer loves mother" who has a good skill level of 84.6% in the pretest and 100% in the posttest. In conclusion, the module for preparing for the role of motherhood effectively increases the knowledge and skills of volunteers who love mothers." Keywords: Skills, Knowledge, Mother's Role, "Volunteer Loves Mother"